Implementasi Transparansi dan Akuntabilitas Dana Zakat Berbasis PSAK 409 dan Kepercayaan Muzakki pada LAZISMU Medan - Ikhlasul Amal; Kamilah Kamilah; Wahyu Syarvina (Jurnal Riset Akuntansi, 2025)
Zakat is a sharia-based social financial instrument whose sustainability of collection is highly dependent on the trust of the muzakki towards the amil zakat institution. This trust is built through transparency and accountability of fund management that refers to the applicable accounting standards for zakat, infaq, and alms, namely PSAK 409. This study aims to analyze the implementation of transparency and accountability of zakat funds based on PSAK 409 and its relationship to the level of trust of muzakki in LAZISMU Medan City. This study uses a qualitative method with a descriptive approach. Data were obtained through in-depth interviews, documentation, and observation of 7 (seven) informants, consisting of 5 (five) administrators/staff and 2 (two) muzakki LAZISMU Medan City, then analyzed using the interactive model of Miles and Huberman. The results of the study indicate that LAZISMU Medan City has implemented transparency of financial reports and accountability of zakat fund management referring to PSAK 409, both from administrative and substantive aspects, including recognition, measurement, recording, distribution, presentation, and disclosure of ZIS funds. This implementation is in line with the Stewardship Theory perspective, where amil acts as a trustworthy steward for the interests of muzakki, thus contributing to building the trust of muzakki to continue distributing zakat, infaq, and alms through LAZISMU Medan City. This study is expected to provide theoretical contributions to the study of sharia accounting in mass organization-based Amil Zakat Institutions, as well as practical contributions to LAZISMU Medan City in strengthening transparency and accountability of zakat fund management.